2017
DOI: 10.15761/tit.1000238
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 improves the suppressive capacity of human regulatory T cells

Abstract: One of the main problems that immunologists have not solved yet involves the immunosuppression of ongoing exacerbated responses, as in transplant rejection and autoimmune diseases. To overcome these difficulties, different approaches have been used including the administration of immunosuppressive drugs, monoclonal antibodies, and more recently, the utilization of cellular therapy. In this last strategy, huTregs have been proposed as a safe tool to control transplant rejection or collateral immune reactions su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Gajardo et al also demonstrated the enhancement of Treg suppressive function by IL-33 [32]. It is notable that the therapeutic effect of IL-33 on Treg has been suggested as a possible treatment tool in the selective treatment of type 1 diabetes [43].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Gajardo et al also demonstrated the enhancement of Treg suppressive function by IL-33 [32]. It is notable that the therapeutic effect of IL-33 on Treg has been suggested as a possible treatment tool in the selective treatment of type 1 diabetes [43].…”
Section: Discussionmentioning
confidence: 97%
“…For induction of type 2 diabetes, animals in diabetic groups were fed with a high-fat diet for one month followed by a low-dose intraperitoneal injection of streptozotocin (35 mg/kg) in a 0.1 M citrate buffer (pH 4.5) [32]. The high-fat diet includes speci c percentages of ingredients mentioned in Table 1.…”
Section: Diabetes Inductionmentioning
confidence: 99%